Lifelong Learning, Participation and Equity
XXVI, 366 p.
Keywords: In many countries, schools, universities and other traditional learning institutions are not providing for the educational needs of all members of the community. In many communities, particularly in regional, rural and disadvantaged areas, there are only limited options for people to undertake learning. Limited participation in learning has the danger of reinforcing people’s alienation from mainstream education and from participation and inclusion in social institutions and economic and community life more generally. This book addresses the challenge of identifying effective ways of accommodating the learning needs of all people and in so doing achieving the goals of lifelong learning for all.